Platform values and democratic elections: How can the law regulate digital disinformation?. Issue 36 (April 2020) - Marsden, Chris; Meyer, Trisha; Brown, Ian
Abstract: This article examines how governments can regulate the values of social media companies that themselves regulate disinformation spread on their own platforms. We use 'disinformation' to refer to motivated faking of news. We examine the effects that disinformation initiatives (many based on automated decision-making systems using Artificial Intelligence [AI] to cope with the scale of content being shared) have on freedom of expression, media pluralism and the exercise of democracy, from the wider lens of tackling illegal content online and concerns to request proactive (automated) measures of online intermediaries. We particularly focus on the responses of the member states and institutions of the European Union. In Section 1, we argue that the apparent significance of the threat has led many governments to legislate despite this lack of evidence, with over 40 national laws to combat disinformation chronicled by March 2019. Which types of regulation are proposed, which actors are targeted, and who is making these regulations? Regulating fake news should not fall solely on national governments or supranational bodies like the European Union. Neither should the companies be responsible for regulating themselves. Instead, we favour co-regulation. Co-regulation means that the companies develop – individually or collectively – mechanisms to regulate their own users, which in turn must be approved by democratically legitimate state regulators or legislatures, who also monitor their effectiveness. In Section 2, we explain the current EU use of Codes of Conduct. In Section 3, we then explain the relatively novel idea that social media content regulation, and specifically disinformation, can be dealt with by deploying AI at massive scale. It is necessary to deal with this technological issue in order to explain the wider content of co-regulatory policy options, which we explain and for which we argue in Section 4 . In Section 5 we explain what this means for technology regulation generally, and the socio-economic calculus in this policy field.